Biosorption of iron ions through microalgae from wastewater and soil: Optimization and comparative study. (February 2021) - Zada, Shah; Lu, Huiting; Khan, Sikandar; Iqbal, Arshad; Ahmad, Adnan; Ahmad, Aftab; Ali, Hamid; Fu, Pengcheng; Dong, Haifeng; Zhang, Xueji
Abstract: Microalgae play a significant role in wastewater and soil-bioremediation due to their low-cost and eco-friendly nature. In this study, 21 strains of microalgae were evaluated during removal of iron Fe 2+ from aqueous solutions. Out of 21 strains, five strains ( S. obliquus, C. fusca, C. saccharophila, A. braunii, and Leptolyngbya JSC-1) were selected based on their comparative tolerance for the iron Fe 2+ . These strains were further studied for their Fe 2+ removal efficiency. The results indicated that the selected strains could maintain normal growth pattern up to 50 ppm of Fe 2+, while the concentration beyond 50 ppm inhibited the growth. The Fe 2+ bio-removal efficiencies from wastewater were 97, 98, 97.5, 99, and 99.9%, respectively. Similarly, in soil the bio-removal efficiencies of the five strains were measured as 76, 77, 76, 77.5, and 79%, repectively. A slight increase in leakage of protein and nucleic acids was observed in all strains, which is unlikely could be the reason of iron exposure as similar pattern was also found in control groups. Current results suggested that the selected five strains have high potential to be used as bioremediation tools for Fe 2+ contaminated water and soil. Graphical abstract: Image 1 Highlights: Eliminating iron by environmental-friendly microorganism algae. Selected novel algae strains display high resistance to iron. Performance of iron bio-removal is enhanced in water compared with soil. Up to 99.9% in water and 75% in soil removal was occurred. Removal acts of algae strains S, O. < C, S. < C, F. < A, B. < L, Jsc-1.